multiply (2x^3-5x^2-x+7) by (3-2x+4x^2) correct answer will be marked brainlist​

Question

multiply (2x^3-5x^2-x+7) by (3-2x+4x^2)
correct answer will be marked brainlist​

in progress 0
Hadley 1 month 2021-08-12T05:43:00+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-12T05:44:07+00:00

    8x⁵-24x⁴+12x³+15x²

    (2x^3-5x^2-x+7) by (3-2x+4x^2)

    0
    2021-08-12T05:44:58+00:00

    Answer:

    8x^5-24x^4+12x^3+15x^2

    Step-by-step explanation:

    = (2x^3-5x^2-x+7) * (3-2x+4x^2)

    = 2x^3(3-2x+4x^2) – 5x^2(3-2x+4x^2) – x(3-2x+4x^2)+7(3-2x+4x^2)

    = (6x^3-4x^4+8x^5) – (15x^2-10x^3+20x^4) – (3x-2x^2+4x^3) + (21-14x+28x^2)

    = 6x^3-4x^4+8x^5-15x^2+10x^3-20x^4-3x+2x^2-4x^3+21-14x+28x^2

    = 6x^3+10x^3-4x^3-4x^4-20x^4+8x^5-15x^2+2x^2+28x^2

    = 12x^3-24x^4+8x^5+15x^2

    = 8x^5-24x^4+12x^3+15x^2

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )